CIJDS 2021
DOI: 10.26772/cijds-2021-04-02-010
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating Youth Restiveness and Leadership Problem in Africa: The Nigeria Experience

Abstract: This research sought to interrogate the implications of youth restiveness on leadership problem in Africa using the Nigeria experience. Three research questions were formulated. 1,000 respondents were sampled from youth in Edo, Delta and Anambra States. The conflict theory was adopted as the theoretical orientation for the study. The quantitative technique which relied on a self-constructed instrument was employed to collect data while the data generated from the field was analyzed with the aid of percentage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…(Degenhardt et al 2019) It sometimes undermines moral restraints and encourages deviant or criminal behavior, especially among youth (Chilo, 2018). Obarisiagbon and Ajayi found out that substance abuse was an important determinant of risky sexual behavior among youths in Benin City, Nigeria (Obarisiagbon and Ajayi, 2019) Researchers in Lagos, Nigeria also showed that Nigerian youths have limited knowledge of the adverse effects of substance abuse and widely abused tobacco, alcohol, opiates, cannabis, amphetamines and benzodiazepines (Odukoya et al 2018). Many of these youths eventually end up abusing more addictive substances (Oshodi et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Degenhardt et al 2019) It sometimes undermines moral restraints and encourages deviant or criminal behavior, especially among youth (Chilo, 2018). Obarisiagbon and Ajayi found out that substance abuse was an important determinant of risky sexual behavior among youths in Benin City, Nigeria (Obarisiagbon and Ajayi, 2019) Researchers in Lagos, Nigeria also showed that Nigerian youths have limited knowledge of the adverse effects of substance abuse and widely abused tobacco, alcohol, opiates, cannabis, amphetamines and benzodiazepines (Odukoya et al 2018). Many of these youths eventually end up abusing more addictive substances (Oshodi et al 2019).…”
Section: Introductionmentioning
confidence: 99%